2013
DOI: 10.1007/s12098-013-1114-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A in Children- Clinical Course, Complications and Laboratory Profile

Abstract: Eventhough hepatitis A infection is a self-limiting disease, extrahepatic manifestations and mortality are not uncommon. All cases should be followed up till complete recovery and only a strong index of suspicion will enable us to recognize the complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…In a recent study on clinical course and complications of Hepatitis A in Indian children only 1.3% of cases were found to develop acute glomerulonephritis due to the virus [2]. Pal et al [3] reported a 3yr old boy with hepatitis A infection along with membranoproliferative glomerulonephritis and stage II encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on clinical course and complications of Hepatitis A in Indian children only 1.3% of cases were found to develop acute glomerulonephritis due to the virus [2]. Pal et al [3] reported a 3yr old boy with hepatitis A infection along with membranoproliferative glomerulonephritis and stage II encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Glomerulonephritis associated with hepatitis A infection is unusual and has been reported in very few studies [2][3][4]. In this article we are reporting two cases of hepatitis A infection presenting as hepatic encephalopathy and glomerulonephritis.…”
Section: Introductionmentioning
confidence: 86%
“…To the Editor: We are humbled and thankful to the authors for their kind perusal of our article [1]. We also accept their valid comments regarding Hepatitis A vaccination.…”
mentioning
confidence: 88%
“…We did not aim at dealing with the aspects of Hepatitis A vaccination, its efficacy and effectiveness. We undoubtedly are aware of the importance of vaccination, especially its role in the developing countries, where the incidence of Hepatitis A is 150 per 100,000 per year [1]. In a study done in Israel, the implementation of the Hepatitis A vaccine led to a drastic decrease in the incidence of Hepatitis A infection.…”
mentioning
confidence: 99%
“…To the Editor: We read with great interest the article by Kumar et al that reported the clinical course, complications and laboratory profile of Hepatitis A in children [1]. Although, they emphasized the hyperendemicity, fatal complications and cost effectiveness of Hepatitis A infection; and importance of improved sanitation and health education for its prevention, the importance of vaccination for preventing and control of Hepatitis A virus infection was not mentioned in their article.…”
mentioning
confidence: 99%